Dampak Keberadaan Tari Ilau dan Bentuk Penyajiannya dalam Masyarakat Salayo - Zora Iriani (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
Ilau dance in Selayo still exists and if there is a man from this village who die in other villages or cities, and the body is rested in the wife or parents house, this dance might be performed. At the time of one hundred days after the man died, Ilau dance is performed to commemorate the good things done by this man. However, this depends also on the families whether they want this dance to be performed or not because they have to kill a cow as the requirement. Actually this is contrary to the religion of Islam, but now it is not a matter of the religion because it has become a culture for society of Selayo.. Key words: Ilau dance